The Connection between Maternal Knowledge and Attitude in Providing Proper Complementary Food for Infants at Ribang Health Center - Arie Diana; Anik Purwati; Maria Veronika Widiatrilupi (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Complementary foods, or MP-ASI (food for babies), play a crucial role in providing essential nutrients for infants and children to meet their growing nutritional needs. The knowledge and attitude of mothers are pivotal factors influencing children's nutrition, as a lack of understanding regarding complementary feeding often leads to malnutrition. One of the primary causes of malnutrition in infants is the improper timing of introducing complementary foods, either too early (before six months of age) or too late. This study aims to analyze the relationship between mothers' knowledge and attitudes regarding the provision of complementary feeding for infants aged 6-12 months at the Ribang Health Center, Muara Uya District, Tabalong Regency, South Kalimantan. The study utilized univariate, bivariate, and chi-square tests to analyze the data. A total of 20 respondents were surveyed, with results indicating that 8 respondents (46.7%) had sufficient knowledge and a good attitude, while 14 respondents (70%) demonstrated a good attitude. The chi-square test revealed a p-value of 0.000 (<0.05) at α = 0.05, supporting the hypothesis that maternal knowledge is significantly related to the provision of complementary feeding. However, the bivariate analysis showed a p-value of 0.163, indicating no significant effect between maternal attitudes and the provision of complementary feeding. In conclusion, while there is a significant relationship between maternal knowledge and complementary feeding, the study found no significant association between maternal attitudes and the timing of complementary feeding based on statistical analysis. This study highlights the importance of improving maternal knowledge in the provision of complementary feeding to ensure proper infant nutrition